2014
DOI: 10.1159/000354323
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Nomograms Predicting Lymph Node Involvement in Patients with Prostate Cancer Undergoing Extended Pelvic Lymph Node Dissection

Abstract: Our aim was to validate Briganti's nomograms predicting the probability of lymph node involvement (LNI) in prostate cancer (PCa). Clinicopathological data of 256 PCa patients who underwent extended pelvic lymph node dissection (ePLND) and radical prostatectomy (RP) were obtained from two Bulgarian institutions. Predicted probabilities of LNI were assessed using Briganti's nomograms based on ePLND. In addition to the established basic LNI predictors, Briganti's nomograms included the number of lymph nodes remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 17 publications
1
18
1
3
Order By: Relevance
“…In the Update Nomogram of Briganti et al [5] , the percentage of positive cores is the most accurate predictor of LNI. This was also confirmed by external validation studies [29,30] . On the flip side, the sentinel nomogram reflects the reality of care.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the Update Nomogram of Briganti et al [5] , the percentage of positive cores is the most accurate predictor of LNI. This was also confirmed by external validation studies [29,30] . On the flip side, the sentinel nomogram reflects the reality of care.…”
Section: Discussionsupporting
confidence: 71%
“…However, the staging accuracy and the rates of LNI patients detected by sPLNDs in the monitored sample compare well with data from other sPLND-experienced centers [13] . Ideally, one should also externally validate the reliability of the sentinel nomogram [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines (EAU, National Comprehensive Cancer Network [NCCN]) recommend performing extended pelvic lymph node dissection for men with high-risk and locally APC treated by RP particularly if the risk for lymph node metastases based on available nomograms is estimated to be !5% despite the fact that there are no data from randomised prospective trials supporting an improvement in outcome with lymph node dissection [10][11][12]. The impact of minimal template versus extended lymph node dissection is not known and the pathological processing and reporting of the dissected material is not well defined.…”
Section: 1mentioning
confidence: 99%
“…o Taxane in men with symptomatic mCRP C who had progressive disease as best response to first-line abiraterone or enzalutamide: 96% o Taxane in men with symptomatic mCRPC and secondary (acquired) resistance or abiraterone first-line of use after progression) by followed response (initial enzalutamide: 90% o Abiraterone or enzalutamide for asymptomatic men with mCRPC progressing on or after docetaxel for mCRPC (without prior abiraterone or enzalutamide): 92% o Abiraterone or enzalutamide for symptomatic men with mCRPC progressing on or after docetaxel for mCRPC (without prior abiraterone or enzalutamide): 76% There were also several notable areas of panellist disagreement including but not limited to: (1) chemohormonal therapy in ''low-volume'' CNPC, (2) treatment of the primary tumour in metastatic disease, (3) radium-223 combination strategies, (4) use of platinum in mCRPC, (5) definition of aggressive variant prostate cancer, (6) use, schedule, and duration of osteoclast-targeted therapies especially in the context of newer survival prolonging mCRPC therapies; (7) use of next-generation imaging; (8) how to advise men with known BRCA2, BRCA1, or ATM mutations; (9) adjuvant RT; (10) when to initiate SRT; (11) definition and treatment for oligometastatic synchronous and metachronous prostate cancer; (12) health status assessment in patients aged !70 yr; and (13) pathology reporting of men undergoing a mCRPC biopsy.…”
Section: Second-line Crpcmentioning
confidence: 99%
“…Briganti et al later updated their analyses by increasing the number of cores taken from biopsy, and they repeatedly emphasized that the inclusion of the percentage of positive cores should be mandatory in the prediction model for lymph node invasion of PCa [7, 19]. Hinev, et al demonstrated that Briganti’s nomograms showed a higher predictive accuracy for lymph node invasion as compared with the Memorial Sloan-Kettering Cancer Center nomogram, which provide predictions without information on biopsy cores [20]. Despite the positive correlation between the percentage of positive cores and the percentage of cancer extent in each positive core, each of the two factors also shows an independent predictive value for the advanced tumor stage and an increased index tumor volume in our entire cohort.…”
Section: Discussionmentioning
confidence: 99%